2003
DOI: 10.1017/s1355617703950065
|View full text |Cite
|
Sign up to set email alerts
|

Narrative and procedural discourse in temporal lobe epilepsy

Abstract: It is well established that some individuals with temporal lobe epilepsy (TLE) demonstrate language deficits at the single word level. However, discourse production rarely has been examined quantitatively within this group. This study compared adult TLE patients with an early seizure onset (< or = age 14 years, n = 27) to a control group (n = 28) on narrative and procedural discourse tasks. As a group, the TLE patients performed normally on the procedural discourse task, but differed significantly from the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 55 publications
3
24
0
1
Order By: Relevance
“…23 Experimental studies have shown that TLE is associated with subtle language disturbances at a discourse level, including longer and more variable pause durations, 44 failure to produce increasingly compact forms of a narrative with repetition, 43 and reduced speech rate, inadequate descriptive detail, and excessive mistakes and repairs. 47 Macrolinguistic dysfunctions of this type have been linked to capacity limitations affecting the multilevel planning of language output. 48,49 This, in turn, implies poor coordination between the neural apparatus of planning, working memory, and selective attention (such as dorsolateral prefrontal cortex, anterior cingulate region) and classic language structures.…”
Section: Functional Consequences Of Altered Resting-state Connectivitymentioning
confidence: 99%
“…23 Experimental studies have shown that TLE is associated with subtle language disturbances at a discourse level, including longer and more variable pause durations, 44 failure to produce increasingly compact forms of a narrative with repetition, 43 and reduced speech rate, inadequate descriptive detail, and excessive mistakes and repairs. 47 Macrolinguistic dysfunctions of this type have been linked to capacity limitations affecting the multilevel planning of language output. 48,49 This, in turn, implies poor coordination between the neural apparatus of planning, working memory, and selective attention (such as dorsolateral prefrontal cortex, anterior cingulate region) and classic language structures.…”
Section: Functional Consequences Of Altered Resting-state Connectivitymentioning
confidence: 99%
“…Given the prevalence of procedural discourse in everyday communication, it is not surprising that it has been a frequently examined discourse genre in both clinical assessment and research of discourse-level performance across a variety of populations including healthy older adults , individuals with traumatic brain injury (TBI) (Hartley & Jensen, 1991;Snow, Douglas, & Ponsford, 1997), aphasia (Ulatowska, Doyel, Stern, Haynes, & North, 1983); Alzheimer's disease (AD) (Ripich, Carpenter, & Ziol, 1997), and temporal lobe epilepsy (TLE) (Bell et al, 2003). The underlying assumption supporting such widespread use of clinical and research tasks designed to tap into procedural and other discourse forms (e.g., narrative, picture description) is that each discourse task places unique linguistic and other cognitive (e.g., memory) demands on the communicator (Shadden, Burnette, Eikenberry, & DiBrezzo, 1991;Ulatowska & Chapman, 1989).…”
Section: Procedural Discoursementioning
confidence: 99%
“…Shadden et al (1991) found that in healthy participants procedural discourse samples were longer and syntactically more complex than narrative or picture description samples. However, attempts to correlate discourse performance post hoc with indices of cognitive ability have yielded modest and variable effects (e.g., Bell et al, 2003;Hartley & Jensen, 1991;Ulatowska et al, 1983) and few attempts have been made to offer a theoretical perspective or description of how various cognitive domains would support distinct aspects of discourse performance across tasks.…”
Section: Procedural Discoursementioning
confidence: 99%
“…Three studies were interested in discourse abilities in TLE and two of them found that the patients performed significantly worse in a narrative discourse task that required description of the sequence of events. [10][11][12] Reasons for linguistic deficits found in patients with TLE are not completely clear, and different hypotheses can be formulated. First, multiple regions of the brain, which may also include the left perisylvian areas critical for language, may be subject to neuronal cell loss and deafferentiation in chronic TLE.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, information about language comprehension, discourse production, repetition, and reading is sparse, and findings are divergent. [11][12][13][14] To our knowledge, to date there are no reports on spontaneous speech or writing abilities in TLE. Thus, studies have very rarely administered tests tapping different language domains in order to provide a linguistic profile of patients with TLE.…”
mentioning
confidence: 95%